Preferences of motorcyclists to views of managed, rural southern United States landscapes. (March 2020) - Merry, Krista; Bettinger, Pete; Siry, Jacek; Bowker, J.M.
Abstract: A survey of motorcyclists was conducted to determine their perception of the quality of views from roads of a managed, rural southern United States landscapes in the winter season. The survey instrument was made available through an advertisement placed in an email newsletter delivered to the members of a motorcyclist organization. While the potential number of respondents was very high, the response rate to the survey was low. We found that respondents generally preferred landscape views with water in the forefront. Landscapes with agricultural land or pasture in the forefront and forest in the background, or that contained mature or young forest in the forefront were preferred to a lesser extent. Landscape views with bare ground in the forefront and forest in the background were the least appealing. However, all types of landscape views, on a scale ranging from very appealing to not appealing at all, at least received neutral mean preference scores from the respondents of the survey. Management implications: The work presented provides a framework for performing a low-cost assessment of landscape aesthetic quality in rural communities specifically for communities that are interested in attracting motorized recreational activities. The population of interests here is motorcyclists but the protocol presented could be applicable to other motorized recreational groups. Municipalities, policy makers, planners, and resource managers interested in attracting this type of tourism need to consider the impacts of scenic driving and motorized recreational activities on infrastructure, natural resources, and road safety.